TECHNOLOGY BURNOUT AMID THE DEMANDS OF ADAB: A PHENOMENOLOGICAL STUDY OF THE LIVED EXPERIENCES OF CONTEMPORARY ISLAMIC SCHOOL TEACHERS IN COPING WITH TECHNOLOGY BURNOUT IN THE EDUCATION 5.0 ERA - Hesti Pusposari; Siti Masruchah (Education Studies and Teaching Journal (EDUTECH), 2026)
The digitalization of education, accelerated by the transition toward the Society 5.0 paradigm, has engendered a novel phenomenon threatening teachers' psychological well-being: technology burnout, a state of emotional and physical exhaustion precipitated by the excessive demands of continuous adaptation to instructional technology devices and systems. For educators in contemporary Islamic schools, this burden is compounded by the responsibility of upholding adab (moral-spiritual exemplary behavior), a function that necessitates a deeply human presence that cannot be supplanted by digital efficiency. This article aims to construct a conceptual framework and a methodological design for a phenomenological study to elucidate teachers' lived experiences of confronting technology burnout amidst the dual demands of technological mastery and the preservation of adab values. Adopting a conceptual review approach, this study synthesizes literature across four distinct domains: burnout and technostress theories, the philosophy of Islamic education concerning adab and ta'dib, the discourse of Society 5.0 in education, and theories on the sustainability of teacher well-being. The proposed methodological framework aligns with the Husserlian descriptive phenomenological tradition, operationalized through Colaizzi’s data analysis method, and adheres to Lincoln and Guba’s criteria for trustworthiness. The synthesis reveals that technology burnout among Islamic school teachers is not merely a matter of technical workload; rather, it represents an existential struggle between maintaining the authenticity of their role as a mu'addib (moral educator) and confronting the structural pressures of rapid digital acceleration. The contribution of this article lies in proposing a novel analytical framework that integrates Hobfoll’s Conservation of Resources (COR) theory with the concept of adab to contextualize teacher burnout, alongside offering policy implications for the sustainable well-being of educators amidst digital transformation. Ultimately, this paper recommends a future empirical research agenda utilizing the newly developed phenomenological interview guide.